A "No‐Touch" Antibody‐Staining Method of Adherent Cells for High‐Throughput Flow Cytometry in 384‐Well Microplate Format for Cell‐Based Drug Library Screening. Issue 8 (26th December 2019) - Cornel, Annelisa M.; Szanto, Celina L.; van Til, Niek P.; van Velzen, Jeroen F.; Boelens, Jaap J.; Nierkens, Stefan
Abstract: In the last decade, screening compound libraries on live cells has become an important step in drug discovery. The abundance of compounds in these libraries requires effective high‐throughput (HT) analyzing methods. Although current cell‐based assay protocols are suitable for HT analyses, the analysis itself is often restrained to simple, singular outcomes. Incorporation of HT samplers on flow cytometers has provided an interesting approach to increase the number of measurable parameters and increase the sensitivity and specificity of analyses. Nonetheless, to date, the labor intensive and time‐consuming strategies to detach and stain adherent cells before flow cytometric analysis has restricted use of HT flow cytometry (HTFC) to suspension cells. We have developed a universal "no‐touch" HTFC antibody staining protocol in 384‐well microplates to bypass washing and centrifuging steps of conventional flow cytometry protocols. Optimizing culture conditions, cell‐detachment and staining strategies in 384‐well microplates resulted in an HTFC protocol with an optimal stain index with minimal background staining. The method has been validated using six adherent cell lines and simultaneous staining of four parameters. This HT screening protocol allows for effective monitoring of multiple cellular markers simultaneously, thereby increasing informativity and cost‐effectiveness of drug screening. © 2019 The Authors. Cytometry Part A published by Wiley Periodicals LLC. on behalf of International Society for Advancement of Cytometry.